PEMANFAATAN TEKNOLOGI PEMBELAJARAN SEBAGAI MEDIA PEMBELAJARAN DALAM MENINGKATKAN MINAT BELAJAR FIQH MUAMALAH SANTRI BAITUL QUR’AN SLOGOHIMO - Rochman, Abdul; Fadhilah, Rif'atul (Rabbani: Jurnal Pendidikan Agama Islam, 2024)
Technology is an important role in world of education today's, the need for technology is very necessary in this era. The Institute can be characterized as an advanced institution, especially in the way that its educators select, classify, and use learning technology as a learning tool. The purpose of this research is to analyze how to use learning technology as a learning tool to increase the interest in learning Fiqh Muamalah among Baitul Qur'an students, which are the obstacles that are asatidz in achieving learning interest and interest in learning. Fiqh Muamalah use and contribution declaration. This research involves the development of effective, creative and innovative knowledge. The method used in this research is descriptive and qualitative data obtained through interviews, observation and documentation. Research results show that the use of learning technology such as learning environments through Canva and Kahoot applications can increase the interest of students in learning, as shown through activity and learning. Treatise on the study of students in learning jurisprudence. The obstacle Asatidz considers to achieve this learning is the necessary preparation of large instruments and needed for internet network. In the meantime, the benefit of using it is that having learned Fiqh Muamalah material is more active, effective, creative and innovative.